COVID-19: NAD+ deficiency may predispose the aged, obese and type2 diabetics to mortality through its effect on SIRT1 activity. (November 2020) - Miller, R.; Wentzel, A.R.; Richards, G.A.
Abstract: The SARS-CoV-2 hyperinflammatory response is associated with high mortality. This hypothesis suggests that a deficiency of nicotinamide adenine dinucleotide (NAD + ) may be the primary factor related to the SARS-Cov-2 disease spectrum and the risk for mortality, as subclinical nutritional deficiencies may be unmasked by any significant increase in oxidative stress. NAD + levels decline with age and are also reduced in conditions associated with oxidative stress as occurs with hypertension, diabetes and obesity. These groups have also been observed to have high mortality following infection with COVID-19. Further consumption of NAD + in a pre-existent depleted state is more likely to cause progression to the hyperinflammatory stage of the disease through its limiting effects on the production of SIRT1. This provides a unifying hypothesis as to why these groups are at high risk of mortality and suggests that nutritional support with NAD + and SIRT1 activators, could minimise disease severity if administered prophylactically and or therapeutically. The significance of this, if proven, has far-reaching consequences in the management of COVID-19 especially in third world countries, where resources and finances are limited.